Profession and Self-Reliance: Female Nurses in Modern Church-Affiliated Hospitals in China - QIAO, Huini (Journal of Research for Christianity in China (JRCC), 2025)
With the introduction of Christianity to China, missionary hospitals practicing Western medicine gradually established themselves across the country. The emergence of Chinese female nurses in these hospitals reflected a shifting public perception of Western medicine and the nursing profession, influenced by the advent of Western medical techniques. In the process of healing and saving lives, female nurses in church hospitals demonstrated their value. While curing illnesses through medical care, they deconstructed traditional local societal perceptions of women. The term “nurse” became increasingly associated with female professions, thereby constructing new social significance for women. By mastering Western medical and nursing techniques, the female cohort in missionary hospitals enabled women in local communities to transcend occupational marginalization. Simultaneously, women gained autonomy and intellectual liberation by breaking free from traditional constraints through their mastery of Western medical care. This advancement significantly propelled the development of the nursing profession and the healthcare sector in modern China.
Keywords: Female Nurse, Church-Affiliated Hospital, Nursing, Social Significance